Association of leukocyte telomere length with the risk of digestive diseases: A large-scale cohort study - Hongqun Yang; Lanlan Chen; Yahui Liu; Jinjiao Li (Chinese Medical Journal)
Abstract. Background:. Leukocyte telomere length (LTL) shortening, a biomarker of telomere attrition, has been linked to multiple diseases. However, the relationship between LTL and digestive diseases remains uncertain. This study aimed to investigate the association between LTL and the risk of digestive diseases. Methods:. A cohort analysis of over 500,000 participants from the UK Biobank (UKB) between 2006 and 2021 was conducted to estimate the associations of LTL with more than 90 common digestive diseases. LTL was quantified using multiplex quantitative polymerase chain reaction, and cases of each disease were determined according to inpatient and primary care data. Multivariable Cox proportional hazards regression analysis was used to evaluate the associations of LTL with the risk of digestive diseases. Furthermore, such associations were also evaluated after stratification by sex and ethnicity. Results:. After a mean follow-up time of 11.8 years, over 20 International Classification of Diseases, 10th Revision (ICD-10) codes were showed to be associated with telomere attrition. LTL shortening is associated with an increased risk of several digestive diseases, including gastroesophageal reflux disease (K21: hazard ratio [HR] = 1.30, 95% confidence interval [95% CI]: 1.19–1.42), esophageal ulcer (K221: HR = 1.81, 95% CI: 1.22–2.71), Barrett’s esophagus (K227: HR = 1.58, 95% CI: 1.14–2.17), gastritis (K29: HR = 1.39, 95% CI: 1.26–1.52), duodenal ulcer (K26: HR = 1.55, 95% CI: 1.14–2.12), functional dyspepsia (K30X: HR = 1.36, 95% CI: 1.06–1.69), non-alcoholic fatty liver disease (NAFLD) (K760: HR = 1.39, 95% CI: 1.09–1.78), liver cirrhosis (K74: HR = 4.73, 95% CI: 3.27–6.85), cholangitis (K830: HR = 2.55, 95% CI: 1.30–5.00), and hernia (K43: HR = 1.50, 95% CI: 1.17–1.94; K44: HR = 1.29, 95% CI: 1.17–1.42). The risk of rectal polyps (K621: HR = 0.77, 95% CI: 0.63–0.92) decreased per unit shortening of LTL. Conclusions:. This study suggests that LTL shortening is associated with an increased risk of most digestive diseases except for rectal polyps. These findings may provide some clues for understanding the pathogenesis of digestive diseases.